(untitled) (CIPEEX, 2026)
Acute myocardial infarction, especially when associated with cardiorespiratory arrest, can trigger neurological complications such as stroke and cognitive deficits, resulting from cerebral hypoxia, hemodynamic instability, metabolic acidosis, and inflammatory activation. Understanding these mechanisms is essential to improving clinical management. This work aimed to analyze the main neurological complications in post-AMI patients. To this end, a literature review was conducted in the PubMed database, using the keywords “neurological,” “myocardial,” and “infarction.” Five free-access articles published between 1992 and 2024 were included. It was observed that AMI is associated with stroke, cognitive deficits, and neurodegenerative changes. The mechanisms involve the activation of the AIM2 inflammasome by cfDNA, an increase in MMP-2/MMP-9, inflammation, and hypercoagulability mediated by factor XIIa, resulting in plaque instability and thrombosis. The time to reperfusion proved to be a determining factor, and therapies targeting AIM2/cfDNA show neuroprotective potential. Therefore, AMI has a strong correlation with severe neurological complications. Rapid reperfusion interventions, hemodynamic monitoring, and neuroprotection strategies can reduce the severity of outcomes. The integration of cardiovascular and neurological assessments, combined with the early identification of risk groups, is essential. Future studies should explore immunomodulatory therapies to optimize functional recovery and neurological prognosis.